Public sector enterprises (PSEs) in post-privatization: Evidence from Pakistan - Naseem Faraz; Ghulam Samad (Journal of Applied Economics, 2022)
Privatization of public-sector enterprises (PSEs) has generated billions of dollars to support fiscal and macroeconomic imbalances in several developing countries. A limited literature evaluates the recent privatization program impacts on the PSEs. This study empirically investigated the privatization impact on the performance and efficiency of the firms in post-privatization period in Pakistan. Firm-level data are used to evaluate the privatization effects on performance and efficiency of the privatized PSEs. We use difference-in-difference approach that exploits within-firm variation in the outcome variables over time. The regression results show that the performance of only few firms improved while it remains negative or insignificant largely. The efficiency of the firms is also not improved significantly in post-privatization period.
Keywords: 330; competition; efficiency; Pakistan; performance; Privatization; regulation policy